Estrogenic activities of diuron metabolites in female Nile tilapia (Oreochromis niloticus) - Boscolo Pereira, Thiago Scremin [UNESP]; Pereira Boscolo, Camila Nomura [UNESP]; Felício, Andreia Arantes [UNESP]; Batlouni, Sergio Ricardo [UNESP]; Schlenk, Daniel; Alves de Almeida, Eduardo [UNESP] (Elsevier, 2016)
Some endocrine disrupting chemicals (EDCs) can alter the estrogenic activities of the organism by directly interacting with estrogen receptors (ER) or indirectly through the hypothalamus-pituitary-gonadal axis. Recent studies in male Nile tilapia (Oreochromis niloticus) indicated that diuron may have anti-androgenic activity augmented by biotransformation. In this study, the effects of diuron and three of its metabolites were evaluated in female tilapia. Sexually mature female fish were exposed for 25 days to diuron, as well as to its metabolites 3,4-dichloroaniline (DCA), 3,4-dichlorophenylurea (DCPU) and 3,4-dichlorophenyl-N-methylurea (DCPMU), at concentrations of 100 ng/L. Diuron metabolites caused increases in E2 plasma levels, gonadosomatic indices and in the percentage of final vitellogenic oocytes. Moreover, diuron and its metabolites caused a decrease in germinative cells. Significant differences in plasma concentrations of the estrogen precursor and gonadal regulator17α-hydroxyprogesterone (17α-OHP) were not observed. These results show that diuron metabolites had estrogenic effects potentially mediated through enhanced estradiol biosynthesis and accelerated the ovarian development of O. niloticus females.
Keywords: Diuron; Diuron metabolites; Endocrine disrupting chemicals; Gametogenesis; Nile tilapia